Reclaiming International Student Mobility in a Post-pandemic World (Comparative & International Education Series, 2022)
International education was thriving pre-pre-pandemic, where massification of international student mobility was evident. An international education experience abroad was sought after by students to enhance their employability, gain global citizenship skills, and contribute to economic prosperity. Since the start of the COVID-19 global pandemic in early 2020, country borders remain closed, closing doors for students to experience international education abroad. This essay reflects international student mobility and prospects for a post-pandemic world. In addition, this essay seeks to find rationales and potential directions to critically address ‘How will international student mobility look like in a post-pandemic world?’ The value of international education will not diminish post-COVID, but it will take a significantly different shape online. Technology might be the leveler that the global higher education landscape requires in reimagining internationalization as a more inclusive experience for all.How to cite in APA: Abdullah, D., & Singh, J. K. N. (2022). Reclaiming international student mobility in a post-pandemic world. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 47-52). STAR Scholars.